2020
DOI: 10.5433/1679-0359.2020v41n1p181
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, morphometry, and membrane integrity of epididymal spermatozoa of spotted pacas (Cuniculus paca, Linnaeus 1766)

Abstract: Morphology, morphometry, and membrane integrity of epididymal spermatozoa of spotted pacas (Cuniculus paca, Linnaeus 1766)Morfologia, morfometria e integridade da membrana de espermatozoides epididimários de paca (Cuniculus paca, Linnaeus 1766) Highlights: Majority (73%) of the epididymal spermatozoa of Cuniculus paca were normal. Proximal cytoplasmic droplet was the second most frequent defect found. Both ACP-123 ® and Botusemen Special ® were efficient extenders. Intra-acrosomal vesicles were observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Basal cells were elongated, with an elongated nucleus, notched nuclear envelope and a scant amount of cytoplasmic organelles. There was a predomination of euchromatin in the nuclear matrix as well [ 57 ].…”
Section: Paca ( Cuniculus Paca )mentioning
confidence: 99%
See 2 more Smart Citations
“…Basal cells were elongated, with an elongated nucleus, notched nuclear envelope and a scant amount of cytoplasmic organelles. There was a predomination of euchromatin in the nuclear matrix as well [ 57 ].…”
Section: Paca ( Cuniculus Paca )mentioning
confidence: 99%
“…They used powdered coconut water (ACP-123) and Botusemen special ® as the extenders for flotation and found that there were no differences in sperm abnormality rates between both extenders, and both preserved the cell membranes. However, ACP-123 preserved 83.8% of viable spermatozoa compared with the Botusemen special ® , which preserved 72.9% [ 57 ].…”
Section: Paca ( Cuniculus Paca )mentioning
confidence: 99%
See 1 more Smart Citation